The effect of green accounting in enhancing financial performance: evidence from audit committee role - Saeed, Paiman; Abdullah, Hariem; Abdulrahman , Rebaz (Humanities Journal of University of Zakho, 2023)
Practicing green accounting and ensuring a company’s compliance with environmental conservation rules and holding it accountable in case of violations are vital steps in reducing pollution. Additionally, management can make informed decisions regarding environmental impacts and cost minimization. Companies report their environmental performance through sustainability reports, which complement financial data. The role of the audit committee is to ensure the integrity and accuracy of financial reports and auditing procedures by confirming the objectivity and independence of external auditors. This study explores how green accounting practices, through the effectiveness of the audit committee, can contribute to improving the financial performance of industrial companies in the Kurdistan region of Iraq. Data is collected from a number of industrial firms in the sectors of oil and gas, petrochemicals, textile, construction materials, cement and metal processing. The results indicate that green accounting positively influences the financial performance of industrial companies. In addition, audit committee positively affects the performance of the sample firms in the Kurdistan Region. Moreover, audit committee moderated the positive relationship between green accounting and financial performance. We recommendations the formation of audit committees in companies with professional and practical qualifications in accounting, and experienced in the implementation of green accounting, and to develop the capabilities of the board of directors for industrial firms to strengthen the committee’s capability to understand and improve the practice of green accounting.